Pengenalan Komik Digital Berbahasa Inggris Sebagai Media Edukasi Peduli Lingkungan Di Forum Anak Kelurahan Sriwedari - Winarti, Winarti; Hidayatulloh, Aris; Akbar, Rama Sultan; Darmawan, Diky (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
This community service program was motivated by the low effectiveness of conventional environmental education methods, as well as the limited English literacy and digital technology utilization among members of the Forum Anak Kelurahan Sriwedari. The children were not yet accustomed to using English in thematic contexts such as environmental issues, even though this ability is essential for broadening their global awareness. The purpose of this program was to develop an innovative learning medium in the form of an English-language digital comic with an environmental theme, designed to enhance both English proficiency and ecological literacy among children. The program employed a Participatory Action Research (PAR) approach, emphasizing active participant involvement throughout all stages—from planning to evaluation. The results showed a significant improvement in environmental vocabulary mastery (from 58 to 84), the ability to construct simple sentences (from 60 to 82), and the confidence to use English in communicative contexts (from 55 to 83). The children also demonstrated higher learning motivation and greater awareness of environmentally friendly behavior. In conclusion, the introduction of English-language digital comics proved effective as a creative learning medium that integrates English language acquisition with Education for Sustainable Development (ESD), fostering the development of globally minded and ecologically conscious young learners.